Flammability and sensitivity of materials in oxygen-enriched atmospheres twelfth volume - Barthélémy, Hervé (ASTM special technical publication, 2010)
"Twenty-eight peer-reviewed papers cover: Ignition and combustion of metals and non-metals ; Oxygen compatibility of components and systems ; Analysis of ignition and combustion ; Failure analysis and safety ; Aerospace and industry oxygen applications ; And more! STP 1522 provides a diverse source of new information to the air separation industry, oxygen manufacturers, manufacturers of components for oxygen and other industrial gases service, manufacturers of materials intended for oxygen and other industrial gases service, and users of oxygen and oxygen-enriched atmospheres. It covers the aerospace, medical, industrial gases, chemical processing, steel and metals refining industries, as well as to military, commercial, and recreational diving."--Publisher's website.